Unpacking the Role of Higher Education Institutions in Accelerating Women’s Progressive Education in Kenya - Odhong, Emily A.; Achieng, Cynthia O. (Journal of Higher Education and Academic Advancement, 2024)
Due to unprecedented global challenges, labour market dynamics, and uncertainties, higher education institutions have no options but to adopt new approaches to enhance adaptability. In Kenya, despite many efforts made to accelerate women's empowerment, only 29 percent of women between the ages of 15 and 49 are empowered. The universities have a unique capacity and potential to develop skills, foster knowledge, and mobilize educational resources. Hence, accelerating an inclusive socio-economic recovery starts with a solid foundation of human capital which entails: health, education, skills, jobs, and growth to boost progressive education.  The significance of the study is to: expand access to progressive quality education for girls and women; inform policies; enhance capacity to upscale women’s holistic learning and most importantly promote resilience and innovativeness among higher education institutions to emerge stronger. The main objective of the study was to analyse the role of higher education institutions in accelerating women’s progressive education in Kenya. The study was anchored on John Dewey's theory and women's empowerment framework, which cuts across and support both dependent and independent variable. The study adopted a mixed-method research design and, a pragmatic and constructive research philosophy. The researcher adopted a triangulation approach in sampling techniques where stratified, purposive, and random sampling techniques were applied.  The study sample size comprised 129 - degree students and 26 lecturers. Questionnaires were adopted as the data collection tool.  Based on the regression results, the study findings reveal that the R-squared is 0.62, the Adjusted R-squared is 0.61, the F-statistic of 31.94, and a p-value of 0.0000. This implies that the model explains 61% of changes in women’s progressive education. The study concludes that the public-private nexus, blended learning, digitalization, and student retention explain a 61% percent change in women’s progressive education. The study recommends: First, strengthening of public-private nexus through institutional industry linkages, upscaling support through adequate funding of women’s education, and considering Students as Partners in their learning. Second, embracing a blended learning approach to reduce the dropout rate of female students and upscale women empowerment through the integration of ICT skills training. Third, institutions should commit adequate resources to promote effective digitalization and improvement in ICT infrastructure that facilitates learning and is user-friendly to lecturers, learners, and administrators. Lastly, promoting students’ retention through mentorship, semester check-ins, workshops, and effective lecturers, to enhance student enrollment and acceleration which increases completion rate and school-to-work transition, and embracing transformative and sustainable leadership.